Proton boron capture therapy: microdosimetry and treatment planning study with boron - Yoo, Seung Hoon; Sedliarou, Ilya; MacDiarmid, Jennifer A.; Brahmbhatt, Himanshu; Han, Soorim; Kim, Kum Bae; Tran, Linh T.; Rosenfeld, Anatoly B.; Kim, Eun Ho; Lin, Yen Hwa; Tan, Wei Sing; Cheah, Ying Ying; et al. (Frontiers in Oncology, 2025)
BackgroundProton-boron capture therapy (PBCT) has been proposed as a method to enhance the biological effectiveness of proton therapy through the p + 11B → 3α nuclear reaction. The resulting alpha particles may increase local radiation quality, but the dosimetric and microdosimetric consequences remain uncertain.MethodsLineal energy distributions were measured using a Silicon-On-Insulator (SOI) microdosimeter under 70 MeV and 190 MeV monoenergetic proton beams delivered with pencil beam scanning. Dose-averaged lineal energy (yD¯) values were derived from oscilloscope signals calibrated against Geant4 Monte Carlo simulations. Measurements were performed at both entrance and Bragg peak depths, with and without boronophenylalanine (BPA) delivered via EnGeneIC Dream Vector (EDV™). In parallel, a treatment planning study was conducted in Eclipse TPS to assess the impact of localized high-density boron regions on dose distributions under conventional and FLASH-simulated delivery, using both fixed and variable RBE models.ResultsFor 70 MeV protons, no significant difference in yD¯ was observed between boron-loaded and control conditions. At 190 MeV, a reproducible increase in yD¯ was detected at the Bragg peak in the presence of boron (p < 0.01), while no effect was observed at the entrance depth. Treatment planning simulations showed that localized boron density improved dose uniformity within the clinical target volume and reduced discrepancies between fixed and variable RBE dose distributions under FLASH conditions.DiscussionThese findings indicate that PBCT can induce detectable increases in microdosimetric lineal energy under high-energy proton beams, even in the absence of macroscopic dose enhancement. The treatment planning results further highlight the potential of boron-enhanced LET modulation in conjunction with FLASH delivery. Together, the study supports continued investigation of PBCT as a strategy to optimize biological effectiveness in proton therapy, with future work focusing on realistic boron distribution models and integration of dose-rate effects.